Mutational spectrum of DNA damage and mismatch repair genes in prostate cancer - Bugoye, Fidelis Charles; Torrorey-Sawe, Rispah; Biegon, Richard; Dharsee, Nazima; Mafumiko, Fidelice M. S.; Patel, Kirtika; Mining, Simeon K. (Frontiers in Genetics, 2023)
Over the past few years, a number of studies have revealed that a significant number of men with prostate cancer had genetic defects in the DNA damage repair gene response and mismatch repair genes. Certain of these modifications, notably gene alterations known as homologous recombination (HRR) genes; PALB2, CHEK2 BRCA1, BRCA2, ATM, and genes for DNA mismatch repair (MMR); MLH1, MSH2, MSH6, and PMS2 are connected to a higher risk of prostate cancer and more severe types of the disease. The DNA damage response (DDR) is essential for constructing and diversifying the antigen receptor genes required for T and B cell development. But this DDR imbalance results in stress on DNA replication and transcription, accumulation of mutations, and even cell death, which compromises tissue homeostasis. Due to these impacts of DDR anomalies, tumor immunity may be impacted, which may encourage the growth of tumors, the release of inflammatory cytokines, and aberrant immune reactions. In a similar vein, people who have altered MMR gene may benefit greatly from immunotherapy. Therefore, for these treatments, mutational genetic testing is indicated. Mismatch repair gene (MMR) defects are also more prevalent than previously thought, especially in patients with metastatic disease, high Gleason scores, and diverse histologies. This review summarizes the current information on the mutation spectrum and clinical significance of DDR mechanisms, such as HRR and MMR abnormalities in prostate cancer, and explains how patient management is evolving as a result of this understanding.